1996
DOI: 10.1093/clinids/23.5.1156
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion to Human Herpesvirus 6 and Human Herpesvirus 7 Among Brazilian Children with Clinical Diagnoses of Measles or Rubella

Abstract: We collected acute-phase and convalescent-phase serum samples from Brazilian patients who presented with exanthem of unknown origin and evaluated these samples by means of an immunoblot assay for seroconversion to human herpesvirus 6 (HIV-6) or human herpesvirus 7 (HIV-7). Measles or rubella had been clinically diagnosed in all these patients, but their sera were negative for antibodies to both measles virus and rubella virus. Twenty percent of the patients clearly seroconverted to HHV-6 after manifestation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 11 publications
1
9
1
1
Order By: Relevance
“…Exanthem subitum is often misdiagnosed as measles or rubella (Black et al, 1996a;Tait et al, 1996;Oliveira et al, 2003) despite its typical clinical features (Juretic, 1963) and the rash has also been confused with allergic reactions to antibiotics (Irving et al, 1990). As regards less easily recognised febrile illnesses, the seminal work of Hall et al (1994) showed that primary HHV-6 infection accounted for 20% of fevers between 6 and 12 months of age.…”
Section: Background-the Need For Diagnosismentioning
confidence: 99%
“…Exanthem subitum is often misdiagnosed as measles or rubella (Black et al, 1996a;Tait et al, 1996;Oliveira et al, 2003) despite its typical clinical features (Juretic, 1963) and the rash has also been confused with allergic reactions to antibiotics (Irving et al, 1990). As regards less easily recognised febrile illnesses, the seminal work of Hall et al (1994) showed that primary HHV-6 infection accounted for 20% of fevers between 6 and 12 months of age.…”
Section: Background-the Need For Diagnosismentioning
confidence: 99%
“…More commonly a mixture of pathogenic bacteria is identified [37] but when a single etiology can be identified the most common pathogens identified include Streptococcus pneumoniae, Haemophilus influenzae, and Staphylococcus aureus [37] [38] [39] [40]. It has also been suggested that MV infection is associated with reactivation of latent Mycobacterium tuberculosis infections [41] and has been linked to reactivation of latent herpes virus infections [42].…”
Section: Clinical Observations In Acute Measles Virus Patientsmentioning
confidence: 99%
“…Further aggravated by malnutrition, secondary infections then often follow a severe or fatal course (Dollimore et al, 1997). Furthermore, persistent infections by other pathogens may be reactivated or exacerbated as a result of MV-induced immunosuppression in children and young adults (Black et al, 1996;Tamashiro et al, 1987). MV was the first pathogen noted to cause immunosuppression, almost a century ago, when von Pirquet first coined the term 'anergy' to describe immunological impairment in a clinical condition when he described the transient loss of delayed-type hypersensitivity responses to tuberculin during measles.…”
Section: Measles Virus: the T-cell Silencing Conceptmentioning
confidence: 99%